Psychometric Properties of the Metacognition Scales about Rumination in Clinical and Non-clinical Turkish Samples - (:unkn) unknown (TURKIYE SINIR VE RUH SAGLIGI DERNEGI, 2015)
Aim: The aim of this study is to examine the reliability and validity of the Turkish adaptations of the Positive Beliefs about Rumination Scale (PBRS) and the Negative Beliefs about Rumination Scale (NBRS) in clinical and non-clinical samples. Method: While the non-clinical sample of the study consisted of 455 participants, the clinical sample was composed of 60 major depressive disorder (MDD), 30 panic disorder (PD) and 30 social anxiety disorder (SAD) cases. Results: The results of the factor analyses confirm the construct validity and original factor structure of the scales. Findings obtained from internal consistency and test-retest analyses indicated good reliability for the scales. Supporting the convergent validity of the scales, the correlations between metacognitions about rumination and depressive symptoms, rumination, metacognidons about worry, pathological worry, and anxiety symptoms were found to be positive and significant in the non-clinical sample. Hierarchical regression analyses demonstrated that both scales have predictive validity for depressive symptoms after controlling for anxiety symptoms. As for extreme group comparisons, it supported the criterion-related validity of the scales. In discriminant clinical validity examinations, although both scales were able to differentiate MDD, PD, and SAD groups from healthy controls, they were unable to differentiate the depressive group from the other anxiety disorder groups. Conclusion: A comprehensive psychometric evaluation of the scales demonstrated that both PBRS and NBRS are reliable and valid assessment devices that can be used for research purposes both in clinical and non-clinical groups in Turkey.
Keywords: Depression; rumination; metacognition; Positive Beliefs about Rumination Scale; Negative Beliefs about Rumination Scale; STATE WORRY QUESTIONNAIRE; DEPRESSIVE RUMINATION; REPETITIVE THOUGHT; SELF-FOCUS; SYMPTOMS; BELIEFS; ANXIETY; MOOD; VALIDATION